2018
DOI: 10.3390/pharmaceutics10040269
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Delivery Methods Using Nanotechnology

Abstract: Pathologies of the brain, of which brain cancer, Alzheimer’s disease, Parkinson’s disease, stroke, and multiple sclerosis, are some of the most prevalent, and that presently are poorly treated due to the difficulties associated with drug development, administration, and targeting to the brain. The existence of the blood-brain barrier, a selective permeability system which acts as a local gateway against circulating foreign substances, represents the key challenge for the delivery of therapeutic agents to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(130 citation statements)
references
References 84 publications
1
129
0
Order By: Relevance
“…The BBB restricts the delivery of therapeutics to the brain. Overall, 98% of sMDs and probably all TPs cannot cross the barrier by free diffusion [31][32][33]. In the last decade, intense investigation allowed the discovery of new strategies to increase brain penetration of existing therapeutics (invasive, pharmacological, and physiological) [34][35][36].…”
Section: Strategies To Overcome the Bbbmentioning
confidence: 99%
“…The BBB restricts the delivery of therapeutics to the brain. Overall, 98% of sMDs and probably all TPs cannot cross the barrier by free diffusion [31][32][33]. In the last decade, intense investigation allowed the discovery of new strategies to increase brain penetration of existing therapeutics (invasive, pharmacological, and physiological) [34][35][36].…”
Section: Strategies To Overcome the Bbbmentioning
confidence: 99%
“…80 On a similar note, other studies also demonstrated that the PEGylation contributed to the BBB permeability of different inorganic nanoparticles like silica nanoparticles, carbon nanotubes, etc. 81 Similarly, Ren and coauthors (2012) also demonstrated the role of PEG functionalization on the brain targeting of the oxidized multiwalled carbon nanotube. The oxidized multiwalled carbon nanotube was surface modified with PEG and angipep-2.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 96%
“…Nanotechnology-based approaches are under intensive study to overcome the blood-brain barrier and deliver the appropriate amount of drug to the specific brain site. Organic nanocarriers include polymeric nanoparticles, liposomes, dendrimers, and micelles, while inorganic nanocarriers include gold nanoparticles, silica nanoparticles, and carbon nanotubes [138]. Further research is expected to understand the blood-brain barrier crossing mechanisms and to improve the efficiency of brain delivery methods using nanotechnology.…”
Section: Kynurenic Acid Analoguesmentioning
confidence: 99%